2004
DOI: 10.1634/stemcells.2004-0094
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Embryonic Stem Cell–Derived Neural Progenitors Improves Behavioral Deficit in Parkinsonian Rats

Abstract: Human embryonic stem cells (hESCs) may potentially serve as a renewable source of cells for transplantation. In Parkinson's disease, hESC-derived dopaminergic (DA) neurons may replace the degenerated neurons in the brain. Here, we generated highly enriched cultures of neural progenitors from hESCs and grafted the progenitors into the striatum of Parkinsonian rats. The grafts survived for at least 12 weeks, the transplanted cells stopped proliferating, and teratomas were not observed. The grafted cells differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
235
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(260 citation statements)
references
References 19 publications
(37 reference statements)
21
235
0
2
Order By: Relevance
“…When undifferentiated hESCs were injected into the hind limb muscles or under the kidney capsule of SCID mice, teratomas were readily formed after 8-12 weeks [Richards et al, 2002] but injection of hESC-derived neurons into the brain of immunosuppressed fetal mice did not result in the formation of any teratomas after 8 weeks [Yang et al, 2008]. In another study, successful hESC-derived neuronal engraftment in a Parkinsonian rat model did not yield teratomas after 12 weeks [Ben-hur et al, 2004]. It is therefore tempting to suggest that the brain may be a tumor-privileged site.…”
Section: Immunorejectionmentioning
confidence: 99%
“…When undifferentiated hESCs were injected into the hind limb muscles or under the kidney capsule of SCID mice, teratomas were readily formed after 8-12 weeks [Richards et al, 2002] but injection of hESC-derived neurons into the brain of immunosuppressed fetal mice did not result in the formation of any teratomas after 8 weeks [Yang et al, 2008]. In another study, successful hESC-derived neuronal engraftment in a Parkinsonian rat model did not yield teratomas after 12 weeks [Ben-hur et al, 2004]. It is therefore tempting to suggest that the brain may be a tumor-privileged site.…”
Section: Immunorejectionmentioning
confidence: 99%
“…Thus, the faster the hESCs are differentiated in vitro, the higher the risk may be of teratoma formation after transplantation [45]. A number of studies have reported the successful engraftment of hESCderived cells within the brain, as treatment for Parkinson's disease and HD, without the formation of tumors [46][47][48]. It is important to note that these studies were conducted in rodents, and did not include the long survival times needed to rigorously assess tumorigenic potential.…”
Section: Embryonic Stem Cells As a Source Of New Medium Spiny Neuronsmentioning
confidence: 99%
“…All of these cell lines were originally propagated on mouse feeder layers, although several have recently been transferred to feeder free support systems (1,3,7,9,12,21). While the differentiation of DA traits in some hES lines has been described previously (4,5,16,17,18,26), with the exception of one study (19) these protocols involve the prolonged use of complex media containing serum or other undefined reagents and/or cell conditioned media (CM) or co-culture with these cells (ie. PA6 mouse stromal cells) (4,5,10,13,16,17,18,22,26).…”
Section: Introductionmentioning
confidence: 99%
“…While the differentiation of DA traits in some hES lines has been described previously (4,5,16,17,18,26), with the exception of one study (19) these protocols involve the prolonged use of complex media containing serum or other undefined reagents and/or cell conditioned media (CM) or co-culture with these cells (ie. PA6 mouse stromal cells) (4,5,10,13,16,17,18,22,26). Since animal cells contain immunogenic antigens that can be incorporated into hES cells (14), they ultimately can cause immune rejection after their transplantation into the brain.…”
Section: Introductionmentioning
confidence: 99%